PENERAPAN KESELAMATAN KERJA DIKAMAR HOTEL KOH TIEN MENG (KTM) RESORT BATAM - ", Ramadania; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Work safety is an activity out in order to avoid the risk of accidents or damage at work, in this case there is a SOP standart operational procedure that regulates it. This research was conducted at KOH TIEN MENG (KTM) Resort Batam in the housekeeping departement with a total of seven key informan room attendants. This study aims to determine how the application of work safety in the hotel room KOH TIEN MENG (KTM) Resort Batam. In this case the researcher uses a qualitative descriptive method to analyze the problem by collecting data or information through interviews, observation and documentation then conclusions can be draw. The result of this study are for the implementation of work safety in KTM Resort Batam hotel room has not been going according to procedures and there needs to be more improvement from both hotel management and employees.Keywords : safety works, housekeeping, roomboy